Multi-objective local environmental simulator (MOLES 1.0) Model specification, algorithm design and policy applications - Tikoudis, Ioannis (OECD Environment Working Papers, 2017)
This paper describes MOLES 1.0, an integrated land-use and transport model developed with Object-Oriented Programming principles in order to combine selected characteristics from Spatial Computable General Equilibrium and microsimulation models